The relationship between extrinsic rewards and employees’ performance among office staff at Universiti Pendidikan Sultan Idris (UPSI) in Tanjong Malim, Perak/ Qairun Najiha Ahmad Fazil - Ahmad Fazil, Qairun Najiha (2018)
Extrinsic reward is a reward that affect employee externally based on what he or she does within an organization. Many researches have shown that extrinsic rewards provide a greater impact in influencing employees to do their best in the job. Therefore, it is very important for an organization to ensure an efficient type of rewards occur throughout the entire organization. But, in selecting the best type of extrinsic rewards is not easy and have encountered many issues between the workers and human resource department. Therefore, this study was conducted to determine the relationship between extrinsic rewards and employees’ performance based on Motivation-Hygiene Theory by Herzberg (1959) which stated that Motivators can motivate an individual such as performance bonuses and Hygiene-factors were said to have a de-motivational value if not present in the organization environment such as salary and working conditions. Questionnaire was used as the instrument in collecting data among respondents which are office staff at a university in Tanjong Malim, Perak. 24 questions were developed and categorized according to respective variables which are performance bonuses, salary, working condition, employees’ performance and also including demographic surveys. A total of 97 questionnaires were valid and had been analyzed to find out the outcomes. All tests were done and the results show that working conditions showed a positive, strong and significant relationship towards employees’ performance (r=0.520, p<0.01). For performance bonuses, the result was positive, moderate and significant relationship towards employees’ performance (r=0.492, p<0.01). For salary, it shows that salary has positive, weak but significant relationship towards employees’ performance (r=0.268, p<0.01). In conclusion, this study determined that performance bonuses, salary and working condition are elements in extrinsic rewards that can affect the productivity of employees.